2010
DOI: 10.1002/dc.21548
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration cytology with histological correlation of chordoma metastatic to the lung: A diagnostic dilemma

Abstract: Chordoma is an uncommon tumor initially believed to be benign due to the rarity of its metastasis. Cytological, morphological, and immunohistochemical features of chordoma, relating to its origin from notochordal remnants, allows for its accurate diagnosis. A 75-year-old man with a known history of tuberculosis (TB) presented with shortness of breath and a dry cough. A chest X-ray demonstrated a diffuse, infiltrative miliary pattern in both lungs. Bronchial washings submitted for culture and cytological examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The findings of Hu et al [ 20 , 21 ] highlight that fibroblast growth factor receptor (FGFR)/ methyl ethyl ketone (MEK)/ extracellular signal regulated kinase (ERK)/brachyury pathway coordinately regulates chordoma cell growth and survival and may represent a novel chemotherapeutic target for chordoma. Jäger et al [ 22 ] suggest that the differential expression of HOX genes in chordomas of the clivus and sacrum suggests an oncofetal mechanism in gene regulation linked to the anatomic site. In the study from Chen et al, [ 13 ] human (hsa-) miR-185-5p was identified as a crucial miRNA in chordoma development via the Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of Hu et al [ 20 , 21 ] highlight that fibroblast growth factor receptor (FGFR)/ methyl ethyl ketone (MEK)/ extracellular signal regulated kinase (ERK)/brachyury pathway coordinately regulates chordoma cell growth and survival and may represent a novel chemotherapeutic target for chordoma. Jäger et al [ 22 ] suggest that the differential expression of HOX genes in chordomas of the clivus and sacrum suggests an oncofetal mechanism in gene regulation linked to the anatomic site. In the study from Chen et al, [ 13 ] human (hsa-) miR-185-5p was identified as a crucial miRNA in chordoma development via the Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 ] Some authors opine that the role of cytology in preoperative diagnosis of chordoma is simple, reliable, and unquestionable. [ 3 4 5 ] On the contrary, Hernández-León et al . [ 6 ] suggest that cytological study of chordoma is not easy, due in part to differential diagnoses considered and to scarce experience with these tumors.…”
Section: Answermentioning
confidence: 99%
“…[ 8 ] The presence of physaliphorous cells is considered as a defining feature for the diagnosis of chordoma. [ 5 ] However, chordoma has been described even in the absence of physaliphorous cells. [ 9 ] Physaliphorous (drop-bearing) cells may be vacuolated in classical variant and eosinophilic and atypical in the chondroid variant.…”
Section: Answers To Additional Questionsmentioning
confidence: 99%
See 2 more Smart Citations